Study on issues of 21st century skills for students of technical and vocational education - Megat Salleh, Nan Nurul Hidayah; Puteh, Saifullizam; Hassan, Nur Farha; Muhammad Sanusi, Amanina (American Scientific Publisher, 2018)
21st century skills should be in line with the transformation of technical and vocational education to produce graduates of quality, knowledge and skills in today's technological development. The purpose of this study is to look at issues in educational institutions for students of technical and vocational education. Instruments used in this study were semi-structured interviews. Respondents for this study are from ministries, academics and industry. The interview was conducted to look into the issue of the 21st century skills of technical and vocational education students. The issues with the 21st century skills for students of technical and vocational education has to be identified in order to improve the current technical and vocational education. There are four issues had been identified which are knowledge, skills, technology and attitude. These issues need to be taken into light to improve the future graduates and current students of Technical and Vocational Education. This is important because the industry needs high quality technical and vocational graduates in terms of knowledge and skills that are high before stepping into the workplace.